Prognostic factors in T3–Т4N0M0 breast cancer - I. V. Vysotskaya; V. P. Letyagin; K. V. Maksimov (Опухоли женской репродуктивной системы)
The study used the records of clinical observations of 145 patients with locally advanced T3–Т4N0M0 breast cancer (BC) who were treated at the N.N. Blokhin Russian Cancer Research Center, Russian Academy of Medical Sciences, in 1998 to 2003. Based on the examined combination of prognostic factors, the authors identified the criteria that had the greatest impact on the prognosis of primary T3–Т4N0M0 BC, which must the standard for its determination in this category of patients.